(untitled) (Alberta Journal of Educational Research, 2002)
The purpose of this study was to investigate relationships between gender and Alberta diploma examination and school-awarded scores. Weak relationships between gender and scores were found both on Alberta diploma examination scores and on school-awarded scores. These relationships tended to be relatively greater in magnitude for school-awarded scores than for diploma examination scores, with girls generally attaining higher school-awarded scores than boys. Effect sizes of all correlations between scores and gender were in the small range. R² values showed that the overall statistical effect of gender on students’ schoolawarded scores was greater than the effect on students’ diploma examination scores. The greatest statistical effect for gender was on the difference between school-awarded scores and diploma examination scores, with girls having larger differences than boys.